THE ADVANTAGES OF THE DISTRIBUTION FUNCTION AS A METHOD OF GRAPHICAL REPRESENTATION OF THE ECONOMIC STRUCTURE OF SOCIETY - V. A. Kapitanov; A. A. Ivanova; A. Yu. Maksimova (Статистика и экономика, 2018)
The aim of the paper is to compare three different methods of graphical representation of the inequality: using frequency polygons, Lorentz curves and distribution functions. It is shown that for the representation of real (i.e. incomplete) data, the last is most appropriate. The method of investigation consists in verifying the conformity of the method of graphical representation of inequality to the following three requirements:1. Insensitivity of the method to the quantization of data.2. Sensitivity to the width of the entire range of income from zero to income of the richest person provided that information about the wealthy members of society might be incomplete.3. Visibility. The curve, describing the inequality must have characteristic points (extremes, bends) so that it can be somehow identified. The presence of features in the economic structure of society must be reflected in the qualitative behavior of the curves. The demand is caused by the necessity to draw a conclusion about the mechanism of the movement of goods in society, which led to the appearance of a curve of exactly this form.The work analyzed direct data on the incomes of Russian citizens published by ROSSTAT (Federal State Statistics Service), Forbes magazine and the Federal Tax Service, indirect data on incomes determined by the distribution of car prices (from two independent sources) and real estate, as well as data from the Credit Suisse Research Institute about property inequality in Russia. The following main conclusions were made. The course of the curves that characterize the real distribution of the population by income, suggests that in society there is only one mechanism for the movement of goods. This is a mechanism of rank exchange, in which the interaction of rich and poor economic agents is characterized by a shift in market prices in favor of the rich and the greater, the more resources the latter has.The frequency polygons (and therefore the histograms) do not correspond to the first requirement, the Lorentz curves for the second and the third and only the distribution functions correspond to all three of the above requirements, and therefore can be recommended as the main method of graphical representation of the inequality.The curves of distribution functions from five independent sources (ROSSTAT and Forbes summary data, ROSSTAT and Federal Tax Service summary data, data from two sources on car prices, real estate prices), built on a single chart, practically coincided. Mutual verification of these data allows us to state that they characterize the true picture of inequality inRussia. ROSSTAT data on inequality are substantially underestimated, as well as the data of the Credit Suisse Research Institute (the latter, to a lesser extent).To assess real inequality, information about the incomes of the richest members of society is important, since 99.976% of the population occupy only 0.0058% of the income scale.